Sistem Kenotariatan Indonesia dalam Perspektif Civil Law Country dalam Mewujudkan Asta Cita Ketujuh dan SDGs 16 serta Keselarasannya dengan Wacana Global Legal Harmonization - Fransiska Ardana (Jurnal Hukum Lex Generalis, 2026)
The Indonesian notarial system, rooted in the Civil Law tradition, places notaries as public officials with broad authority in the creation of authentic deeds that have full evidentiary force. In the context of national development, strengthening the notarial system is crucial to realising the first of the Eight Goals, namely the enforcement of fair, humane and ethical law, as well as supporting the global agenda through SDG point 16 on peaceful, inclusive and accountable institutions. This study uses a literature review method by examining regulations, doctrines, and comparisons of notarial practices in civil law countries such as the Netherlands, France, and Germany. The results of the study show that although the position of notaries in Indonesia is equivalent to that in civil law countries in terms of status and the power of deeds, there are still weaknesses in the aspects of digitisation, supervision, and professional education. To that end, strengthening the notarial profession through e-notary regulations, integration with e-Government, improving professional ethics, and technology-based supervision are urgent needs. With these measures, the notarial profession can become the front line in strengthening preventive legal certainty, promoting a healthy investment climate, and building legal institutions with integrity in accordance with the first Asta Cita mandate and SDG point 16.